FRENCH AS A LANGUAGE OF DIPLOMACY AND CULTURE - Khodjayeva Khurshida Sharafitdinovna; Merzaitova Hilola (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes the role of language in the development of state structures and international relations. In particular, it examines the significance of the French language in diplomacy and international communication, its historical development, and its current status in global diplomatic affairs. The study also emphasizes the practical use of language in diplomatic processes and the necessity of proficiency in French for those engaged in diplomacy. The article highlights the historical legacy, diplomatic terminology, cultural influence, and practical application of French in international organizations.